2022
DOI: 10.1002/cti2.1407
|View full text |Cite
|
Sign up to set email alerts
|

An autologous colonic organoid‐derived monolayer model to study immune: bacterial interactions in Crohn's disease patients

Abstract: Objectives Crohn's disease (CD) initiation and pathogenesis are believed to involve an environmental trigger in a genetically susceptible person that results in an immune response against commensal gut bacteria, leading to a compromised intestinal epithelial barrier and a cycle of inflammation. However, it has been difficult to study the contribution of all factors together in a physiologically relevant model and in a heterogenous patient population. Methods We develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Recent studies suggest IBD-PDOs and non-IBD-PDOs have distinct phenotypes with respect to transcriptional signatures 39 and baseline permeability. 40 However, transcriptional variation in our study was more strongly associated with growth media, culture conditions, and donor variability than with disease status ( Figure 3A ). Moreover, control- and IBD-PDOs consistently formed monolayers with stable TEER that were impermeable to 0.4 kDa Lucifer yellow ( Figure 5 and S5 ).…”
Section: Discussionmentioning
confidence: 59%
“…Recent studies suggest IBD-PDOs and non-IBD-PDOs have distinct phenotypes with respect to transcriptional signatures 39 and baseline permeability. 40 However, transcriptional variation in our study was more strongly associated with growth media, culture conditions, and donor variability than with disease status ( Figure 3A ). Moreover, control- and IBD-PDOs consistently formed monolayers with stable TEER that were impermeable to 0.4 kDa Lucifer yellow ( Figure 5 and S5 ).…”
Section: Discussionmentioning
confidence: 59%
“…Testing of current medications on patient-specific organoids will optimize treatment for patients, reduce therapy failure and mitigate adverse effects [15]. Organoids can be used to produce colonic monolayers where the individual effects of immune cells and bacteria can be assessed in CD patients [24]. Additionally, organoids offer a new https://doi.org/10.46889/JRMBR.2024.5102 https://athenaeumpub.com/journal-of-regenerative-medicine-biology-research/ therapeutic approach to reconstruct the epithelial barrier in the inflamed mucosa of IBD patients to accelerate healing through engraftment onto damaged epithelium [16,19].…”
Section: Discussionmentioning
confidence: 99%
“…T cells are known to drive the pathogenesis of intestinal inflammatory disorders due to excessive cytotoxicity and production of pro-inflammatory cytokines. T cells and organoids have been co-cultured indirectly using transwell systems (with T cells cultured in the basolateral chamber) [87], or directly by embedding both populations in an ECM [88,89]. Using the indirect coculture method, it was demonstrated that secretion of inflammatory mediators by T cells is sufficient to destroy colonoid monolayers [87].…”
Section: Epithelial Cell-cell Interactionsmentioning
confidence: 99%
“…T cells and organoids have been co-cultured indirectly using transwell systems (with T cells cultured in the basolateral chamber) [87], or directly by embedding both populations in an ECM [88,89]. Using the indirect coculture method, it was demonstrated that secretion of inflammatory mediators by T cells is sufficient to destroy colonoid monolayers [87]. An autologous co-culture system (cell populations obtained from the same patient) was developed to study disease and patient-specific interactions between mucosal lymphocytes and enteroids [88].…”
Section: Epithelial Cell-cell Interactionsmentioning
confidence: 99%